Breast cancer radiotherapy and heart disease - Taylor, C; Carolyn Taylor (2008)
Introduction: Some past breast cancer radiotherapy regimens led to an increased risk of death from heart disease. Although heart dose from breast cancer radiotherapy has generally reduced over the past few decades, there may still be some cardiac risk. Estimation of future risk for women irradiated today requires both measurement of their cardiac dose and dose-response relationships, which depend on cardiac dosimetry of past regimens, in conjunction with long-term follow-up data. Methods: Virtual simulation and computed tomography 3-dimensional treatment planning on a representative patient were used to estimate mean heart and coronary artery doses for women irradiated since 1950 in 71 randomised trials in the Early Breast Cancer Trialists’ Collaborative Group (EBCTCG) overview. Patient-to-patient variability in cardiac dose was assessed. Heart and coronary artery doses were also calculated for breast cancer radiotherapy regimens used since the 1950s in Sweden. Cardiac doses from contemporary (year 2006) radiotherapy were assessed for 55 patients who received tangential breast cancer irradiation at a large UK radiotherapy centre. The maximum heart distance (i.e. the maximum distance between the anterior cardiac contour and the posterior tangential field edges) was measured for the left-sided patients, and its value as a predictor of cardiac doses assessed. Results: Mean heart dose for women irradiated in the EBCTCG trials varied from <1 to 18 Gray, and mean coronary artery dose from <1 to 57 Gray. Patient-to-patient variability was moderate. Mean heart dose for women irradiated in Sweden since the 1950s varied from <1 to 24 Gray, and mean coronary artery dose from <1 to 46 Gray. Heart dose from tangential irradiation has reduced over the past four decades. However, mean heart dose for left-sided patients irradiated in 2006 was 2 Gray and around half of them still received >20 Gray to parts of the heart and left anterior descending coronary artery. For these patients, maximum heart distance was a reliable predictor of cardiac doses. For the other patients, mean heart dose varied little and was usually less than 2 Gray. Conclusions: Cardiac doses from breast cancer radiotherapy can be estimated reliably and are now available for use in deriving dose-response relationships in the EBCTCG data and in a Scandinavian case-control study. Cardiac dose has reduced over the past four decades. Therefore the cardiac risk is also likely to have reduced. Nevertheless, for some patients, parts of the heart still receive >20 Gray in the year 2006.